EVALUATION OF MALIGNANCY UNDERESTIMATION IN BREAST PAPILLARY LESIONS DIAGNOSED AT PERCUTANEOUS BIOPSY IN A SOUTH BRAZILIAN ANATOMOPATHOLOGICAL LABORATORY CENTER - Lapa, Flávia da Rocha; Coelho, Karina Munhoz de Paula Alves; Tavares, Lara Cristina de Carvalho; Brusamarello, Aneline (Mastology, 2026)
Objective: The aim of this study was to discover the percentage of patients who underwent surgery due to a biopsy with a diagnosis of papillary lesion and who had their diagnosis underestimated for cancer, analyzing the biopsy data and comparing it with the post-surgical results in the past 10 years. Methods: Anatomopathological examinations of percutaneous core-type or vacuum breast biopsy between 2010 and 2020 with a result of the papillary lesion were analyzed and compared with the anatomopathological result obtained surgically. Cases in which the biopsy already demonstrated malignancy were excluded. The data were from the CEDAP (Centro de Diagnósticos Anátomo-Patológicos) pathological anatomy laboratory database in Joinville, Santa Catarina. Results: In the reported period, 126 biopsies were recorded with a diagnosis of breast papillary lesion. Of these, 21 were excluded because they did not meet the established criteria. In the follow-up examinations of the papillary lesions after surgery, 76 (72.4%) corresponded to benign lesions, including 30 cases demonstrating atypia, and 29 (27.6%) to carcinomas, of which 14 corresponded to invasive lesions and 15 in situ carcinomas. Conclusion: Papillary breast lesions are a diagnostic challenge in a biopsy, requiring sequential surgical excision, even though this practice is being questioned nowadays, due to the high risk of underestimation.